2017
DOI: 10.1017/s0022149x1700044x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of digenean metacercariae within bream (Abramis brama) gill apparatus: preferences, co-occurrence and interactions of parasites

Abstract: Species-specific microenvironmental preferences and interactions between parasite species have been the focus of many ecological studies. Here, we studied the distribution of ectoparasite species within the gill apparatus of bream (Abramis brama) from Lake Lubāns (Latvia) to establish whether digenean metacercariae: (1) prefer specific patches within the gill apparatus; (2) co-occur in the same patches with monogeneans and copepods within a host individual; and (3) interact with monogeneans and copepods. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In Poland, at least 13 species of freshwater fish species, such as crucian carp, barbel, common bream, blue bream, white bream, common dace, ide, common roach, The parasite was also found in southern Ukraine by Goncharov and Soroka (2015) which is the southernmost record. The Latvian finding of P. ovatus (see Zolovs et al 2018) is probably the northernmost record of this species. (The finding of P. ovatus from the heart of grayling, Thymallus thymallus, in northern Norway by Ieshko et al 2001 seems quite unusual.)…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In Poland, at least 13 species of freshwater fish species, such as crucian carp, barbel, common bream, blue bream, white bream, common dace, ide, common roach, The parasite was also found in southern Ukraine by Goncharov and Soroka (2015) which is the southernmost record. The Latvian finding of P. ovatus (see Zolovs et al 2018) is probably the northernmost record of this species. (The finding of P. ovatus from the heart of grayling, Thymallus thymallus, in northern Norway by Ieshko et al 2001 seems quite unusual.)…”
Section: Discussionmentioning
confidence: 90%
“…In Poland, at least 13 species of freshwater fish species, such as crucian carp, Carassius carassius (Linnaeus, 1758); barbel, Barbus barbus (Linnaeus, 1758); common bream, Abramis brama (Linnaeus, 1758); blue bream, Ballerus ballerus (Linnaeus, 1758); white bream, Blicca bjoerkna (Linnaeus, 1758); common dace, Leuciscus leuciscus (Linnaeus, 1758); ide, Leuciscus idus (Linnaeus, 1758); common roach, Rutilus rutilus (Linnaeus, 1758); rudd, Scardinius erythrophthalmus (Linnaeus, 1758); European perch, Perca fluviatilis Linnaeus, 1758; ruffe, Gymnocephalus cernua (Linnaeus, 1758); northern pike, Esox lucius Linnaeus, 1758; and tench Tinca tinca (Linnaeus, 1758) have hitherto been reported as the second intermediate hosts of this parasite (Grabda 1971, Sobecka et al 2004, Linowska and Sobecka 2015. Paracoenogonimus ovatus has also been reported from common bream in Latvia (Zolovs et al 2018), from western tubenose goby, Barbatula barbatula (Linnaeus, 1758), in Russia (Zhokhov et al 2017), from stone loach, Cobitis taenia Linnaeus, 1758, in Russia (Mineeva 2016, Shershnevaa andZhokhov 2013); from common roach, white bream, common bream, rudd, northern pike, Prussian carp, Carassius gibelio (Bloch, 1782), and pike-perch, Sander lucioperca (Linnaeus, 1758) in Mykolaiv region, Ukraine (Goncharov and Soroka 2015). Ieshko et al (2001) found P. ovatus on the heart of grayling, Thymallus thymallus (Linnaeus, 1758), in northern Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Microhabitat preferences may be selected to maximise initial infection success, total growth and reproduction or subsequent transmission (Montgomery and Roloff 2017; Poulin 2005; Sukhdeo and Sukhdeo 1994). Previous studies of parasites have highlighted the importance of host microhabitat (i.e., within-host factors), such as the local availability of resources, intra- and interspecific competition, immune defenses, temperature and pH (Friesen et al 2018; Holmes 1973; Jensen and Johnsen 1992; Zolovs et al 2018). For example, the nematode Heligmosomoides polygyrus specifically establishes within regions of the mouse small intestine with the longest villi, thereby providing worms with greater attachment opportunities (Bansemir and Sukhdeo 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The factors that influence how parasites select their hosts are often complex and depend on the attributes of both the host and the parasite (Dick and Patterson 2007;Johnson et al 2019;Sukhdeo and Sukhdeo 1994). Some parasites are generalists in their use of host individuals or species (Woolhouse et al 2001), such as the apicomplexan Toxoplasma gondii that can infect nearly all warm-blooded vertebrate taxa, from wolves (Canis lupus) to Hawaiian monk seals (Monachus schauinslandi) (Dubey 2021;Dubey et al 2020). However, many parasites exhibit specificity for hosts as a function of species identity or individual host characteristics (e.g., sex, life stage or body size) (Johnson et al 2019;Johnson and Hoverman 2014;Lewis et al 2002;Manzoli et al 2021;Sukhdeo and Sukhdeo 1994) (see Combes (1991) for a review of the encounter and compatibility filters between parasites and their host).…”
Section: Introductionmentioning
confidence: 99%